HUMAN AND PORCINE FVIII INHIBITOR RESPONSE FOLLOWING INFUSION OF HUMAN FVIII CONCENTRATE - MEASUREMENT USING AN AGAROSE GEL SYSTEM - Perry, D J; Hill, F G H (Thrombosis and Haemostasis, 1987)
Conventional methods for determining inhibitor levels in haemophiliacs are time consuming and labour intensive. The agarose gel technique of Jorquera et al. (1) has been modified and standardized to measure human and porcine inhibitors to VIII:C.26 samples from 12 haemophiliacs with inhibitors were analysed and in all cases antibody to human and porcine VIII:C was detected.Six haemophiliac patients with 'high responder-type' inhibitors were studied using stored plasma and the rise in antibody titres to both human and porcine VIII:C was determined sequentially during treatment with human FVIII concentrate.One patient (J. C.) had received a single treatment with porcine concentrate (Hyate:C) with no rise in porcine VIII:C.In 5 of 6 patients both porcine and human inhibitor titres rose but the porcine levels were less than the human. However, in the remaining high responder patient (I. I.) with previously mild haemophilia and no exposure to porcine FVIII, the rise in porcine antibody titre greatly exceeded that of human. This patient has continued to be treated with human FVIII concentrate during which time the human inhibitor titres have fallen more than the porcine.This method is simple to perform and has the advantage that both human and porcine inhibitor titres can be easily and quickly assessed so that the most appropriate therapy can be given.1. Jorquera JI, Carmona E, Aznar JA, Peiro A and Sanchez-Cuenca JM. (1985) A Standardized Method for Measuring Anti-FVIII:C Inhibitors in Haemophilia A by Coagulation Inhibition in Agarose Gel. Thromb. Haemostas. 54(2): 377-380.